Epigenetic regulation of MED12: a key contributor to the leukemic chromatin landscape and transcriptional dysregulation - Arundhati Chavan; Cassidy Jones; Whit Lawrence; Samrat Roy Choudhury (Epigenetics & Chromatin)
Abstract Background MED12 is a key regulator of transcription and chromatin architecture, essential for normal hematopoiesis. While its dysregulation has been implicated in hematological malignancies, the mechanisms driving its upregulation in acute myeloid leukemia (AML) remain poorly understood. We investigated MED12 expression across AML subgroups by integrating chromatin accessibility profiling, histone modification landscapes, and DNA methylation (DNAm) patterns. Functional assays using DNMT inhibition were performed to dissect the underlying regulatory mechanisms. Results MED12 shows subtype-specific upregulation in AML compared to hematopoietic stem and progenitor cells, independent of somatic mutations. Chromatin accessibility profiling reveals that the MED12 locus is epigenetically primed in AML blasts, with increased DNase hypersensitivity at regulatory elements. Histone modification analysis demonstrates strong H3K4me3 and H3K27ac enrichment around the transcription start site (TSS), consistent with promoter activation, while upstream and intragenic regions exhibit enhancer-associated marks (H3K4me1, H3K27ac). Notably, hypermethylation within TSS-proximal regulatory regions (TPRRs)—including promoter-overlapping and adjacent CpG islands—correlates with ectopic MED12 overexpression, challenging the canonical view of DNAm as strictly repressive. Functional studies show that DNMT inhibition via 5-azacytidine reduces MED12 expression despite promoter demethylation in cells with hypermethylated TPRRs, suggesting a noncanonical role for DNA methylation in maintaining active transcription. Furthermore, MED12 expression positively correlates with DNMT3A and DNMT3B expression, implicating these methyltransferases in sustaining its epigenetic activation. Conclusion This study identifies a novel regulatory axis in which aberrant DNA methylation, rather than genetic mutation, drives MED12 upregulation in AML. Our findings suggest that TPRR hypermethylation may function noncanonically to support transcriptional activation, likely in cooperation with enhancer elements. These results underscore the importance of epigenetic mechanisms in AML and highlight enhancer-linked methylation as a potential contributor to oncogene dysregulation. Future studies should further explore the role of noncanonical methylation-mediated gene activation in AML pathogenesis and therapeutic targeting.